Between skins : the body in psychoanalysis--contemporary developments - Diamond, Nicola (Chichester, West Sussex : Wiley-Blackwell, 2013)
Between Skins challenges individualistic accounts of the body in psychoanalysis. Drawing on philosophy, contemporary neurobiology and developmental research, Nicola Diamond explores the ways in which bodily processes and skin experience are inseparable from the field of language and environmental context. The first book to address epistemological implications for a new understanding of the body and embodiment - offers a new perspective on the division between mind, body and world.
pt. 1. The framework : neuroscience and interdisciplinary connections -- pt. 2. The vital order : moving away from interiority and biology as bedrock -- pt. 3. Exteriority : the body surface.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Body image; Human body; Somesthesia; Body schema -- Psychological aspects; Mind and body; Psychoanalysis; PSYCHOLOGY -- Personality; Electronic books